Novel Magnetic‐Luminescent Janus Nanoparticles for Cell Labeling and Tumor Photothermal Therapy. Issue 39 (21st August 2017) - Wu, Qiang; Lin, Yining; Wo, Fangjie; Yuan, Yufeng; Ouyang, Qingling; Song, Jun; Qu, Junle; Yong, Ken‐Tye
Abstract: Magnetic‐luminescent nanocomposites have multiple uses including multimodal imaging, magnetic targeted drug delivery, and cancer imaging‐guided therapies. In this work, dumbbell‐like MnFe2 O4 –NaYF4 Janus nanoparticles are synthesized via a two‐step thermolysis approach. These synthesized nanoparticles exhibit stability in aqueous solutions and very low cytotoxicity after poly(acryl amide) modification. High cellular uptake efficiency is observed for the folic acid‐conjugated MnFe2 O4 –NaYF4 in human esophagus carcinoma cells (Eca‐109) due to the upconversion luminescence properties as well as the folate targeting potential. The MnFe2 O4 –NaYF4 also strongly absorbs light in the near‐infrared range and rapidly converts to heat energy. It is demonstrated that Eca‐109 cells incubated with MnFe2 O4 –NaYF4 are killed with high efficiency after 808 nm laser irradiation. Furthermore, the growth of tumors in mice (grown from Eca‐109 cells) is highly inhibited by the photothermal effects of MnFe2 O4 –NaYF4 efficiently. Histological analysis reveals no pathological change and inflammatory response in heart, liver, spleen, lung, or kidney. The low toxicity, excellent luminescence, and highly efficient photothermal therapy properties of MnFe2 O4 –NaYF4 Janus nanoparticles illustrated in this work support their vast potential for nanomedicine and cancer therapy. Abstract : A new type of magnetic‐luminescent (MnFe2 O4 –NaYF4 ) multifunctional nanoparticles combining optical property and high photothermal efficiency is successfully synthesized via a two‐step thermolysis approach. The in vitro and in vivo results demonstrate that the obtained nanoparticles may have great potential as theranostic agents for cell labeling and cancer photothermal therapy with low toxicity.